Q: How do you solve 6r plus 713 plus 7r?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

You are searching for the value of r.-7r + 6 = 9 - 6r + 1Notice the 9 and the 1 on the right side. Since they are common factors (terms not attached to x), they can be added.-7r + 6 = -6r + 10Subtract 6 from both sides to eliminate the 6 on the left.-7r = -6r + 4Add 7r to both sides, leaving r-terms on only one side.0 = r + 4Subtract 4 from both sides, so one side is constant and the other is the variable.-4 = rThe answer is -4 is equal to r.

Simplified its 12r+3s

9r-1?

7r = 3r - 527r (- 3r) = 3r - 52 (- 3r)4r = - 524r / 4 = -52 / 4r = -13

if the x in the formula means multiply (next time please use * to denote multiplication) then: 7r-38

Related questions

If that's the equation 6r + 7 = 13 + 7r, r = -6

You are searching for the value of r.-7r + 6 = 9 - 6r + 1Notice the 9 and the 1 on the right side. Since they are common factors (terms not attached to x), they can be added.-7r + 6 = -6r + 10Subtract 6 from both sides to eliminate the 6 on the left.-7r = -6r + 4Add 7r to both sides, leaving r-terms on only one side.0 = r + 4Subtract 4 from both sides, so one side is constant and the other is the variable.-4 = rThe answer is -4 is equal to r.

Simplified its 12r+3s

how do i solve -3r+3r=-6(7+7r)-7(4-7r)

I think so.r2 + 7r + 6 = [ (r+6) (r+1) ]

2r + 7r - 6t - r + 7t = 8r + t

9r-1?

7r = 3r - 527r (- 3r) = 3r - 52 (- 3r)4r = - 524r / 4 = -52 / 4r = -13

12 + 8r - 6 = 7r - 5 - 3 8r +6 = 7r -8 r = -14

if the x in the formula means multiply (next time please use * to denote multiplication) then: 7r-38

(r + 1)(2r + 5)

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc.